Ultrastructural investigation methods for Trypanosoma brucei. - Höög, J; Gluenz, E; Vaughan, S; Gull, K (2010)
Trypanosoma brucei is a unicellular parasite causing African sleeping sickness in cattle and humans. Due to the ease with which these cells can be cultured and genetically manipulated, it has emerged as a model organism for the kinetoplastids.In this chapter we describe the preparation of T. brucei for transmission electron microscopy. A thorough explanation of conventional sample preparation through chemical fixation of whole cells and detergent extracted cytoskeletons followed by dehydration and Epon embedding is given. We also introduce a novel high-pressure freezing protocol, which followed by rapid freeze substitution and HM20 embedding generates T. brucei samples displaying good cell morphology, which are suitable for immunocytochemistry.